Planning Scheme of Shenzhen Airport East Comprehensive Transportation Hub for Air-Rail Intermodal Integration - LIU Yalong; TAN Guowei (Chengshi guidao jiaotong yanjiu)
Objective In recent years, China actively promotes the development of air-rail intermodal transportation. However, as a complex system with aviation and high-speed rail two major external transportation modes meeting, the construction and management of air-rail integrated comprehensive transport hub are extremely challenging. In view of the fact that China is still in the initial stage of exploration in this field, it is particularly important to conduct in-depth research on the planning and construction strategy of air-rail intermodal integrated comprehensive transportation hub. Method Taking Shenzhen Airport East Hub as a specific case, focusing on the common problems prevailing in the planning stage, such as the spatial layout optimization of hub facilities and the improvement of traffic organization efficiency, corresponding planning strategies and implementation schemes are proposed. Result & Conclusion The planning of air-rail intermodal integrated comprehensive transportation hub should take the port-city integration, seamless air-rail connection, and convenient-efficient transportation as the core objectives. Specifically, the integrated development of hub and urban space shall be coordinated through the concept of port-city integration; Guided by the integration of air-rail intermodal transportation, the overall spatial layout of the hub shall be scientifically planned; At the same time, relying on the transportation integration strategy, the transportation system within the hub shall be efficiently organized to ensure smooth conversion and efficient operation of various transportation modes.